2015
DOI: 10.1155/2015/439253
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Polylactic Acid/Candeia Essential Oil Mats Obtained by Electrospinning

Abstract: This work aims to evaluate the effect of inclusion of different contents of candeia (Eremanthus erythropappus) essential oil (whose alpha-bisabolol is the main terpene) on the properties of polylactic acid (PLA) nanostructured mats and their relationship with fiber morphology and structure. The interaction occurring between the PLA and the candeia essential oil was confirmed by thermal and microscopy analysis. Addition of candeia essential oil increased nanofiber diameter and decreased the glass transition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 41 publications
7
21
1
Order By: Relevance
“…This indicates that the crystallization of PLA becomes easier due to the increased chain mobility caused by the Plai oil. This similar effect was also observed in candeia oil loaded PLA fiber mat [37] and PLA/essential oil (i.e., bergamot, lemongrass, rosemary, or clove oil) blends [38].…”
Section: Preparation and Characterization Of Oil Loaded Electrospun Fsupporting
confidence: 73%
“…This indicates that the crystallization of PLA becomes easier due to the increased chain mobility caused by the Plai oil. This similar effect was also observed in candeia oil loaded PLA fiber mat [37] and PLA/essential oil (i.e., bergamot, lemongrass, rosemary, or clove oil) blends [38].…”
Section: Preparation and Characterization Of Oil Loaded Electrospun Fsupporting
confidence: 73%
“…SEM images showed that the bead-free and porous morphology of nanofibre mats are preserved but the collagen nanofibre diameter increased from 342 nm, to 471 nm for collagen nanofibres loaded with thyme essential oil and to 580 nm for collagen nanofibres loaded with oregano essential oil, in agreement with phenol content. The influence of essential oil on nanofibre diameter increase was found also for clove essential oil included in electrospun poly(ε-caprolactone)/gelatin nanofibres [63], fish oil encapsulated in poly(vinyl alcohol) nanofibres [64] and candeia essential oil included in polylactic acid nanofibres [65] and was attributed to electrical conductivity and viscosity changes. EDX analyses confirmed higher concentration of carbon in essential oil loaded nanofibres, with higher values for oregano oil loaded nanofibres.…”
Section: Discussionmentioning
confidence: 68%
“…Data obtained in this study indicated that the average fiber diameter slightly decreased with the addition of PEP from 1.6 ± 0.2 to 0.9 ± 0.2 µm ( Table 1). This could be due to the plasticizer effect of the essential oil (Mori et al, 2015). In this regard, PEP might be acting as a plasticizer, altering the order between single polymer chains and resulting in the decrease of solution viscosity.…”
Section: Discussionmentioning
confidence: 99%